Development of biotic stress resistant F1 interspecific hybrid rootstock derived from Solanum lycopersicum and Solanum habrochaites - Aylin Kabaş; Ibrahim Celik (Acta Scientiarum Polonorum: Hortorum Cultus, 2021)
Tomato is major horticultural plant consumed worldwide. Biotic stress (nematodes, fungus and bacteria) has negative effect on tomato production due to causing reduced yield or plant death. Rootstocks confer resistance to soil-borne pathogen are considered the most effective and environment friendly approach for such a stress management. Thus, development of genetic resources having multiple resistance genes is essential for sustainable tomato breeding. Solanum habrochaites is one of the most studied wild tomato species due to its high genetic potential for biotic and abiotic stresses. In the present study, rootstock potential of an interspecific F1 hybrid derived from S. habrochaites was evaluated as using resistance genes (Frl, I-2, I-3, Mi-3, Pto Ty-1, Ty-3 and Sw-5) specific molecular markers for 6 major tomato diseases and 31 fruit quality traits. The study reported that F1 hybrid had resistance alleles for 5 genes (Frl, I-2, I-3, Pto and Sw-5) confer resistance to fusarium crown rot disease, crown – root rot disease, race 2 and 3 of Fusarium oxysporum f. sp. radicis lycopersici, bacterial speck and tomato spotted wilt virus (TSWV), respectively. Despite high performance of F1 hybrid for biotic stress, the study pointed S. habrochaites specific graft incompatibility due to poor rate of grafting efficiency, small fruit formation and low yield. This is the first comprehensive study evaluated the horticultural performance of an interspecific hybrid in tomato.